Differences in the indicators of inflammation between patients with bipolar and unipolar depression: Inflammation indicators in bipolar and unipolar depression - Pantović Stefanović, Maja; Dodic , Sara; Puric, Marija; Gostiljac, Marta; Nesic, Milica; Dunjic-Kostic, Bojana; Mandic-Maravic, Vanja; Eric, Emilija; Ivkovic, Maja (Medical Research, 2024)
Introduction/Aim: Patients with bipolar disorder, unrecognized and with a delayed onset of manic or hypomanic episodes, are often mistakenly diagnosed with unipolar depression (UD) due to shared symptomatology. The two disorders, however, have related but not identical etiopathogenesis. Alterations of the immune system might play a crucial role in both the onset and manifestation of these conditions. This study aims to compare immune markers between patients with bipolar depression (BD) and UD, and explore their association with acute episode characteristics and disease progression. Material and Methods: This retrospective study included patients with BD (n=60) and UD (n=242), hospitalized within a two-year period, for whom socio-demographic information, acute episode and course of illness characteristics, as well as indicators of inflammation were available. Results: Patients with BD exhibited elevated mean platelet volume (MPV) compared to those with UD. MPV levels correlated with clinical characteristics in both groups; higher MPV was observed in UD patients with earlier age of onset and longer duFration of illness. In BD patients, elevated MPV was associated with psychopathology severity, particularly in individuals with a history of suicide attempts and prolonged duration of untreated disorder. Conclusion: The study indicates the presence of chronic low-grade inflammation in specific subpopulations of patients with affective disorders. Immune changes are distinct in regard to the polarity of the disorder and could be a potential indicator of the severity of psychopathology and illness chronicity.